2019
DOI: 10.7554/elife.46440
|View full text |Cite
|
Sign up to set email alerts
|

Host-pathogen coevolution increases genetic variation in susceptibility to infection

Abstract: It is common to find considerable genetic variation in susceptibility to infection in natural populations. We have investigated whether natural selection increases this variation by testing whether host populations show more genetic variation in susceptibility to pathogens that they naturally encounter than novel pathogens. In a large cross-infection experiment involving four species of Drosophila and four host-specific viruses, we always found greater genetic variation in susceptibility to viruses that had co… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(38 citation statements)
references
References 78 publications
0
38
0
Order By: Relevance
“…The distribution of survival proportions ( Figure 1A) found in the genome wide association study indicates the presence of substantial genetic variation for defense against Enterococcus faecalis in Drosophila melanogaster even after controlling for the effects of infection date, infector identity and Wolbachia status. Since E. faecalis is present in wild populations of D. melanogaster [14], this genetic variance may have arisen due to selective pressure exerted in nature [42]. Resistance, whereby the host works to clear an infection; and tolerance, whereby the host works to limit the damage caused by infection; can both be evolutionary stable strategies for hosts, and selection will promote whichever strategy (or combination of strategies) optimizes fitness [9,43].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The distribution of survival proportions ( Figure 1A) found in the genome wide association study indicates the presence of substantial genetic variation for defense against Enterococcus faecalis in Drosophila melanogaster even after controlling for the effects of infection date, infector identity and Wolbachia status. Since E. faecalis is present in wild populations of D. melanogaster [14], this genetic variance may have arisen due to selective pressure exerted in nature [42]. Resistance, whereby the host works to clear an infection; and tolerance, whereby the host works to limit the damage caused by infection; can both be evolutionary stable strategies for hosts, and selection will promote whichever strategy (or combination of strategies) optimizes fitness [9,43].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the extent of the selection pressure exerted specifically by E. faecalis as opposed to other bacterial pathogens that Drosophila encounter in the wild is an open question, which will be influenced by numerous factors including pathogen encounter rates, pathogen infectivity and pathogen virulence. It may be that selection acts largely at the level of pathogen type (e.g., viral, bacterial, fungal, macro-parasitic), or at the level of classes within these classifications (e.g., Gram-positive vs Gram-negative bacteria, DNA vs RNA viruses) [42,44]. This could explain why one of the main classes of immune response genes in Drosophila, the antimicrobial peptides, are thought to have rather broad-spectrum activities [45,46] rather than targeting specific pathogens [22,47].…”
Section: Discussionmentioning
confidence: 99%
“…[4]. According to Duxbury et al [48], who studied the phenomenon of host-pathogen coevolution, genetic variation in susceptibility to infection in natural populations increases as a result of selection by pathogens. On the other hand, genetic variation of pathogens also increases, so that virulence adapts to host population genetics.…”
Section: Influence Of Evolutionary Historymentioning
confidence: 99%
“…While it is recognized that there is a relationship between virus virulence/pathogenicity and co-adaptation to plant hosts (Sacristan and Garcia-Arenal, 2008), information regarding how viruses apply selective pressure to alter plant susceptibility is not known. A study of Drosophila and its host-speci c viruses found that coevolution may cause sustained genetic variation in susceptibility (Duxbury et al, 2019). This may explain why a southern African cassava landrace is highly susceptible to SACMV that appears to have migrated south from its origin, suspected to be in east Africa or the south-west Indian Ocean islands such as Madagascar (De Bruynet al, 2016) that geographically separated from the African continent (Lefeuvreet al 2007).…”
Section: The M Esculentat200 Mee3l Encodes a Truncated Ring-less Promentioning
confidence: 99%